Low-Frequency Noise Measurements for Electromigration Characterization in BEOL Interconnects - Beyne, S.; Croes, K.; Pedreira, O. Varela; Arnoldi, L.; van der Veen, M. H.; De Wolf, I.; Tokei, Zs (IEEE International Integrated Reliability Workshop final report, 2019)
In this paper we discuss a new EM test methodology, based on low-frequency noise (LFN) measurements. The main advantages of LFN over the standard accelerated EM tests are that they are non-destructive, much faster, closer to operation conditions and provide more fundamental understanding. Using the LFN technique, we study the EM properties in sub-30 nm line-width Cu interconnects with various metallization schemes. Furthermore, the EM activation energies of alternative metal interconnects (Ru, Co, W) are studied by means of LFN measurements.